2016
DOI: 10.4996/fireecology.1202028
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Application of Fuel Reduction Treatments in the Southern Appalachian Mountains, USA: Implications for Achieving Management Goals

Abstract: Fire and resource managers of the southern Appalachian Mountains, USA, have many questions about the use of prescribed fire and mechanical treatments to meet various land management objectives. Three common

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 27 publications
3
52
0
Order By: Relevance
“…); the second burn (March 2006) produced flame heights generally <1.5 m; and the average temperature 30 cm aboveground was 155°C in B and 222°C in MB plots (Waldrop et al. ). The third and fourth burns were low‐intensity, producing flame lengths <2 m; however, measurements of fire temperature were not collected.…”
Section: Methodsmentioning
confidence: 99%
“…); the second burn (March 2006) produced flame heights generally <1.5 m; and the average temperature 30 cm aboveground was 155°C in B and 222°C in MB plots (Waldrop et al. ). The third and fourth burns were low‐intensity, producing flame lengths <2 m; however, measurements of fire temperature were not collected.…”
Section: Methodsmentioning
confidence: 99%
“…During the first prescribed burns (Mar 2003), flame lengths of 1–2 m occurred throughout all burn units, but flame lengths reached up to 5 m in localized spots within blocks, where topography or intersecting flame fronts contributed to erratic fire behavior (Waldrop et al ). Loading of fine woody fuels on mechanical + burn units, where the shrub layer was felled, was approximately double that on control and burn‐only sites.…”
Section: Methodsmentioning
confidence: 99%
“…Average fire temperature at 30 cm aboveground was much hotter in mechanical + burn than burn‐only (370°C and 180°C, respectively). The second burn (Mar 2006) was less intense, with flame lengths generally <1.5 m. Average temperature 30 cm aboveground was 155°C in burn‐only units and 222°C in mechanical + burn units (Waldrop et al ). We did not measure fire temperatures in the third and fourth burns, but we observed that they were low‐intensity with flame lengths <2 m.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations